Developing gender-equitable ecological restoration initiatives: A synthesis of guidance to improve restoration practice - Dick Frederiksen, Sebastian; Elias, Marlène; Zaremba, Haley; Aynekulu, Ermias (2021)
Ecological restoration has the potential to contribute to all Sustainable Development Goals (SDGs). Yet, social issues, including gender relations, often remain unaddressed in ecological restoration initiatives. As the UN Decade on Ecosystem Restoration begins, it is critical to learn from existing knowledge and experiences to restore degraded lands in ways that enhance the equity of restoration, and ensure that restoration initiatives and agendas leave no one behind. This 'guide to guides' places existing resources and guidance materials (frameworks, tools, guidelines, and manuals) designed to enhance equity in restoration initiatives in a common 'Reach, Benefit, Empower, Transform' framework, and highlights the strengths that different resource materials bring to understanding and planning for gender-equitable restoration. As per the framework, the guide provides actionable strategies and recommendations for the design, implementation, and monitoring, evaluation, learning and impact assessment (MELIA) of gender-equitable restoration initiatives. The ultimate goal is to enhance the equity and sustainability of restoration initiatives and allow restoration to achieve its full potential to advance all the SDGs.